PENDAPATAN DAN EFESIENSI HOME INDUSTRI TAHU DI DESA KUNIR KIDUL KABUPATEN LUMAJANG - Rozi Arisyika Putra; Zainal Arifin; Muhammad Sri Wahyudi Suliswanto (Jurnal Ilmu Ekonomi JIE, 2020)
This study aims to analyze the Income and Efficiency of Tofu Home Industry in Kunir Kidul Village, Lumajang Regency. This research is descriptive with a Case Study approach. The results of the study of Revenue Analysis and Efficiency of Tofu Industry Home in Kunir Kidul Village regarding the average income in one month was Rp. 10,920,000 / month with production costs incurred in the amount of Rp. 4,885,573 and make a profit of Rp. 6,034,427. In the calculation of business efficiency or R / C the value is 2.24. The Tofu Industry in Kunir Kidul Village can be said to be efficient and menguntungkn and feasible to run.